Neutralization of Chlamydia trachomatis in cell culture. - Howard, L V (1975)
Neutralization of Chlamydia trachomatis was assayed by the decrease in inclusion-forming units in baby hamster kidney cells grown in culture. Five percent fresh guinea pig sera increased neutralization titers of rabbit antisera 100- to 1,000-fold but had no effect when normal rabbit sera were tested. Neutralization of a type A or B trachoma isolate was strain specific. Neutralization by human eye secretions and sera also was demonstrated when guinea pig sera were included in the test. All of the six human sera tested showed strain specificity against types A or B, in agreement with typing by the fluorescent antibody technique.